Strategi Komunikasi Pemasaran Sasada Kopi dalam Membangun Daya Saing di Industri Coffeeshop - Lubis, Bintang Faturrahman; Barus, Rehia Karenina Isabella (Universitas Medan Area, 2025)
Competition in the coffee shop industry is getting tighter, encouraging business actors to implement effective marketing communication strategies to maintain their existence. This study analyzes Sasada Kopi's marketing communication strategy with the 7P Marketing Mix approach, which includes products, prices, distribution, promotions, people, processes, and physical facilities. Using a qualitative descriptive method, this study collected data through in-depth interviews with Sasada Kopi management, direct observation in the store, and analysis of social media content and customer reviews. The results of the study show that Sasada Kopi has succeeded in maintaining competitiveness through a combination of digital marketing strategies, product quality, and service innovation. However, several challenges were identified, such as a lack of digital content innovation, changes in social media algorithms, and price competition with competitors. Therefore, Sasada Kopi needs to continue to innovate in digital marketing and promotion strategies to remain relevant in this industry.